2014
DOI: 10.3892/etm.2014.1469
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy analysis of three-year subcutaneous SQ-standardized specific immunotherapy in house dust mite-allergic children with asthma

Abstract: The present study aimed to evaluate the efficacy of three-year subcutaneous SQ-standardized specific immunotherapy (SCIT) in house dust mite (HDM)-allergic children with asthma. Ninety children with allergic asthma to HDMs, with or without allergic rhinitis, were randomly divided into two groups, the treatment group and the control group. The treatment group received SCIT combined with standardized glucocorticoid management and the control group received standardized glucocorticoid management alone for a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In a randomized trial that included monosensitized, asthmatic children, SCIT significantly improved asthmatic symptoms and reduced drug intake, associated with a significant decrease in non-specific bronchial hyper-responsiveness [134]. Similar results were observed in other randomized studies, with reduction in fluticasone propionate doses [135], mean medication scores [136], and a higher percentage of patients who discontinued ICS therapy [137,138]. In a prospective study comparing the efficacy of treatment with SCIT or ICS for one year in children with asthma, it was reported that the number of emergency room visits for asthma attacks was significantly lower in the SCIT group than in the ICS group; in addition, pulmonary function was significantly improved in the SCIT group [139].…”
Section: Pediatric Populationssupporting
confidence: 70%
“…In a randomized trial that included monosensitized, asthmatic children, SCIT significantly improved asthmatic symptoms and reduced drug intake, associated with a significant decrease in non-specific bronchial hyper-responsiveness [134]. Similar results were observed in other randomized studies, with reduction in fluticasone propionate doses [135], mean medication scores [136], and a higher percentage of patients who discontinued ICS therapy [137,138]. In a prospective study comparing the efficacy of treatment with SCIT or ICS for one year in children with asthma, it was reported that the number of emergency room visits for asthma attacks was significantly lower in the SCIT group than in the ICS group; in addition, pulmonary function was significantly improved in the SCIT group [139].…”
Section: Pediatric Populationssupporting
confidence: 70%
“…Fourteen studies reported on this outcome . (Table ) Pooled data from six studies suggested no clear benefit of AIT with an SMD of 0.48 (95% CI −0.21, 1.18; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-induced allergic reactions may be serious, as anaphylactic shock may lead to patient fatality (13). Establishing a sensitive and reliable animal model for the study of allergic anaphylaxis is necessary; as a basis for screening and discovering drug allergens in addition to the investigation of drug-induced allergic reaction mechanisms, that are relevant to the prevention and treatment of clinical allergic reactions to drugs (14). However, during the preclinical safety evaluation of drugs, allergic reaction is among the most difficult factors to predict due to the lack of appropriate models for predicting clinical allergic reactions (15).…”
Section: Discussionmentioning
confidence: 99%